2019
DOI: 10.1186/s41687-019-0138-x
|View full text |Cite
|
Sign up to set email alerts
|

Content validity of the Migraine-Specific Quality of Life Questionnaire version 2.1 electronic patient-reported outcome

Abstract: Purpose A concept elicitation, cognitive debriefing, and usability study was undertaken to: 1) ascertain the migraine experience with a particular focus on the impact on roles and daily functioning; 2) determine the comprehensiveness and comprehensibility of the Migraine-Specific Quality of Life Questionnaire version 2.1 electronic patient-reported outcome Role Function-Restrictive (MSQ v2.1 ePRO RFR) domain items, and the appropriateness and understanding of the recall period, response options, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…It simply requires a few seconds to remember" [62]. Participants indicated recall accuracy as a concern only for recall periods greater than one week (e.g., 4 weeks [63]).…”
Section: I) Duration Should Capture Important Effectsmentioning
confidence: 99%
“…It simply requires a few seconds to remember" [62]. Participants indicated recall accuracy as a concern only for recall periods greater than one week (e.g., 4 weeks [63]).…”
Section: I) Duration Should Capture Important Effectsmentioning
confidence: 99%
“…The present study evaluated for the first time the features of single migraine attacks in patients treated with OBT-A, who used an innovative method to report the severity of acute symptoms in real-time [12].…”
Section: Discussionmentioning
confidence: 99%
“…A smartphone app named Aid Diary was specifically designed for this study, by Terin Consortium () It was built to be easy to use, with an obligatory sequence of questionnaires to tick in order to send a complete report; the questionnaires presented in order are: Visual Analogue Scale (VAS) for pain (Figure 2), Allodynia Questionnaire [8,13,18,19], a list of vegetative symptoms associated with migraine attack (nausea, vomiting, phono-photophobia) [11,12], and an image of the head, neck and other parts of the body, in frontal and posterior view, where the patient had the possibility to click exactly on the sites where he/she perceived the pain, to render a report of the extension of headache according to precise and predetermined coordinates (Figure 3). For allodynia, 12 total symptoms were reported, in accordance with previous studies [8,13,18,19], so the final score between 0 and 12 indicated the number of acute allodynia features.…”
Section: Methodsmentioning
confidence: 99%
“…The MSQv2 has three HRQoL dimensions: RR, RP, and EF [22]. The RR dimension has seven items and measures migraine impact on normal activities such as work, productivity, daily activities, energy, tiredness, concentration, leisure, and relationships [14,23]. The RP dimension has four items and measures the impact of migraine on interrupting performance of normal activities [14].…”
Section: Description Of Msqv2mentioning
confidence: 99%
“…The EF dimension has three items and measures migraine's effect on emotional function [14]. The questionnaire consists of 14 questions about migraine attacks during the past 4 weeks, with six response options at each question, ranging from 1 to 6 (1, none of the time; 2, a little bit of the time; 3, some of the time; 4, a good bit of the time; 5, most of the time; and 6, all of the time), and scored linearly on a 0-100 scale where higher scores indicate better HRQoL [23,24]. The minimum clinically important difference for within-group analyses are 5 points, 5-7.9 points, and 8-10.6 points for RR, RP, and EF, respectively [25].…”
Section: Description Of Msqv2mentioning
confidence: 99%